Humor w memach internetowych związanych z pandemią koronawirusa: analiza wybranych przykładów = Humour in internet memes related to the coronavirus pandemic: an analysis of selected examples - Karczewska, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 2020 the coronavirus pandemic dominated global life bringing fear and death. Apart from the health crisis, a significant economic and social turmoil appeared following restrictions implemented worldwide to prevent the spread of the virus. One of the ways to cope with this stressful situation is humour giving relief and offering a chance to see reality from a distance. Therefore, numerous internet memes were created to depict everyday life in the pandemic reality in a humorous way.
Keywords: linguistic humour; coronavirus; internet memes; pandemic; community; humor językowy; koronawirus; memy internetowe; pandemia; społeczność